The Impact of the Budget Deficit on the Effectiveness of Monetary Policy (International Journal of Scientific Trends, 2026)
The interaction between fiscal and monetary policy is a central issue in both macroeconomic theory and policy. A budget deficit, especially when persistent, can affect the effectiveness of central bank instruments through several channels: pressure on interest rates, debt “monetization,” and impacts on the availability of financial resources within the economy. This article aims to theoretically and empirically assess how and to what extent the budget deficit influences the effectiveness of monetary policy, to determine how these effects depend on institutional characteristics, and to provide practical recommendations for coordinating fiscal and monetary policies.